2019
DOI: 10.1111/febs.14746
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial ROS production by HIC‐5: a common feature of oncogene‐induced senescence and tumor invasiveness?

Abstract: Transformation by the ras oncogene can result in promotion of metastasis as well as induction of senescence via increased tissue remodeling, for example, by matrix metalloproteases. Increased production of mitochondrial reactive oxygen species (mtROS) via NADPH oxidase 4 (NOX4) is implicated in this process. Hydrogen peroxide‐inducible clone‐5 (HIC‐5) is postulated to sense both matrix detachment of transformed cells and intracellular ROS and can inhibit ras signaling via inhibition of NOX4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As mentioned before, oncogene-induced senescence causes the upregulation of SASP components via TOR-autophagy spatial coupling compartment [198,200]. In recent years, several reports have demonstrated that oncogene-induced senescence is usually observed in benign tumors where it does control tumor growth and transformation [244][245][246][247][248][249][250]. Doppler and Jansen-Durr stressed out that the transformation triggered by the Ras-oncogene can promote metastasis as well as induction of senescence via increased tissue remodeling such as matrix metalloproteases [245].…”
Section: Resveratrolmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned before, oncogene-induced senescence causes the upregulation of SASP components via TOR-autophagy spatial coupling compartment [198,200]. In recent years, several reports have demonstrated that oncogene-induced senescence is usually observed in benign tumors where it does control tumor growth and transformation [244][245][246][247][248][249][250]. Doppler and Jansen-Durr stressed out that the transformation triggered by the Ras-oncogene can promote metastasis as well as induction of senescence via increased tissue remodeling such as matrix metalloproteases [245].…”
Section: Resveratrolmentioning
confidence: 92%
“…In recent years, several reports have demonstrated that oncogene-induced senescence is usually observed in benign tumors where it does control tumor growth and transformation [244][245][246][247][248][249][250]. Doppler and Jansen-Durr stressed out that the transformation triggered by the Ras-oncogene can promote metastasis as well as induction of senescence via increased tissue remodeling such as matrix metalloproteases [245]. In another study, Volonte et al showed that a lack of caveolin-1 expression can suppress oncogenic K-Ras (K-RasG12V)-induced premature senescence in mouse embryonic fibroblasts and normal human bronchial epithelial cells.…”
Section: Resveratrolmentioning
confidence: 99%
“…In turn, c‐MYC negatively regulates p15 Ink4b and p21 Cip1 expression (Baba et al, 2022 ; Bird et al, 2018 ; Senturk et al, 2010 ; Seoane & Gomis, 2017 ). In line with the literature, we found positive transcriptional activity for NOX4 in mSMCCs (Figure 4c ), downregulation of c‐MYC (Figure 3a ), G1 phase synchronized cancer cells (Figure 4d ), and upregulation of the CDK inhibitory genes p15 Ink4b and p21 Cip1 (Figure 4e,f ); the upregulation of hydrogen peroxide‐inducible clone 5 ( HIC5 ) (Figure 4g ), a sensor of free radicals and an antagonist of NOX4 (Desai et al, 2014 ; Wolfgang Doppler, 2019 ), confirmed the tissue response to NOX4 activation. Notably, NOX4 as a downstream effector of TGFβ1 might coordinate additional functions in mSMCCs not related to cell‐cycle arrest, like EMT, tissue remodeling, and angiogenesis (Chen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we also observed that NOX4 is essential for TGF-β-mediated regulation of MMP9 expression. Interestingly, it has been proposed that NOX4 and associated reactive oxygen species (ROS) regulate MMP9 expression both at promoter activation and mRNA stability levels [ 49 , 50 ]. Poorly studied in the context of the TGF-β actions in cancer, MMP9 has been described as an essential regulator of proteins involved in actin polymerization and cell migration during TGF-β-induced EMT in epithelial cells [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%